Client Experiences of Videocall Therapy During Covid-19 Restrictions in Aotearoa New Zealand - Jones, Amelia (Auckland University of Technology, 2022)
Intermittent restrictions on personal movement were introduced in Aotearoa New Zealand from March 2020, in response to the COVID-19 global pandemic. Phone or online delivery of psychotherapy, psychology and counselling services (telepsychology) became the norm, often facilitated by videocall technology. Whilst there is literature exploring therapists' experiences of videocall therapy, there are relatively few international studies on clients’ experiences. This research aims to describe six clients’ experience of videocall therapy during COVID-19 restrictions in Aotearoa New Zealand. Recruited via social media advertisements, participants shared their experiences in semi-structured interviews. Reflexive thematic analysis of the interviews identified that videocall therapy is commonly thought of as a conceptual ‘space’ defined by safety and containment. It is created by manipulating a client’s external environment, as well as practices from therapists and clients that acknowledge that videocall therapy is a fundamentally different experience to in-person therapy. Findings from the analysis contribute to the knowledge base in this area, suggesting that perceptions of therapeutic efficacy in videocall therapy may be influenced by practices before, during, and after therapy sessions. Though limited by a small sample size, these findings are the first in Aotearoa New Zealand to describe client experiences of videocalltherapy during the period in which COVID-19 restricted therapy in-person.